Characterization of the Ryanodine Receptor Gene With a Unique 3′-UTR and Alternative Splice Site From the Oriental Fruit Moth. Issue 1 (5th February 2016) - Sun, L. N.; Zhang, H. J.; Quan, L. F.; Yan, W. T.; Yue, Q.; Li, Y. Y.; Qiu, G. S.
Abstract: The ryanodine receptor (RyR), the largest calcium channel protein, has been studied because of its key roles in calcium signaling in cells. Insect RyRs are molecular targets for novel diamide insecticides. The target has been focused widely because of the diamides with high activity against lepidopterous pests and safety for nontarget organisms. To study our understanding of effects of diamides on RyR, we cloned the RyR gene from the oriental fruit moth, Grapholita molesta, which is the most serious pest of stone and pome tree fruits throughout the world, to investigate the modulation of diamide insecticides on RyR mRNA expression in G. molesta ( Gm RyR). The full-length cDNAs of Gm RyR contain a unique 3′-UTR with 625 bp and an open reading frame of 15, 402 bp with a predicted protein consisting of 5, 133 amino acids. Gm RyR possessed a high level of overall amino acid homology with insect and vertebrate isoforms, with 77–92% and 45–47% identity, respectively. Furthermore, five alternative splice sites were identified in Gm RyR. Diagnostic PCR showed that the inclusion frequency of one optional exon (f) differed between developmental stages, a finding only found in Gm RyR. The lowest expression level of Gm RyR mRNA was in larvae, the highest was in male pupae, and the relative expression level in male pupae was 25.67 times higher than that of in larvae. The expression level of Gm RyR in the male pupae was 8.70 times higher than in female pupae, and that in male adults was 5.70 times higher than female adults.